(untitled) (Orthodontic Journal of Nepal, 2018)
A case report is presented with Class I malocclusion, moderate lower anterior crowding, maxillary dental midline shift with missing right lateral incisor. The adult orthodontic case was treated comprehensively with the extractions of lower lateral incisor, and upper and lower left first premolars as the balancing extraction. Remarkable improvements were achieved in facial profile, axial anterior inclination, esthetic smile and midline correction in short treatment time. Thus, it is concluded that lower incisor extraction in moderate lower anterior crowding and midline shift yield better and stable results with minimal intervention in select cases.